How Instrumental Leadership Promotes Affective Commitment: Social Skills as Mediator - Mhamed, El Mustapha Ait Sidi; Riggio, Ronald E. (WILEY, 2025)
Employee-organization linkages have been the subject of considerable scholarly and managerial attention. The findings of this research study provide empirical evidence that instrumental leadership attributes predict affective commitment among employees in their organizations. More specifically, based on their expertise and environmental knowledge, instrumental leaders endorse attributes that help followers adhere to the organization's vision through providing timely feedback and facilitating tasks. Instrumental leadership thus promotes a positive workplace in which affective commitment is encouraged. The sample included 226 followers from a major telecom company in Morocco. Employees reported their levels of affective commitment, completed the Social Skills Inventory, and rated their supervisor's instrumental leadership. Results suggest that instrumental leadership may play a role in building employees' affective commitment and that more socially skilled employees may be more likely to develop healthy leader-follower relationships, resulting in affective commitment to the organization as a whole.
Keywords: TRANSFORMATIONAL LEADERSHIP; ORGANIZATIONAL COMMITMENT; JOB-SATISFACTION; PERFORMANCE; EMERGENCE; EMPLOYEE; WORKERS; ORDER; Business & Economics